Safety and Tolerability of Fremanezumab for the Prevention of Migraine: A Pooled Analysis of Phases 2b and 3 Clinical Trials. Issue 6 (12th April 2019) - Silberstein, Stephen D.; McAllister, Peter; Ning, Xiaoping; Faulhaber, Nicola; Lang, Nicole; Yeung, Paul; Schiemann, Jimmy; Aycardi, Ernesto; Cohen, Joshua M.; Janka, Lindsay; Yang, Ronghua
Abstract : Objective: Presentation of pooled analysis of safety data for fremanezumab in patients with chronic (CM) or episodic migraine (EM) from 4 placebo‐controlled phase 2b and phase 3 studies. Background: There is a need for an effective, safe, and well‐tolerated preventive therapy that specifically targets the pathophysiology of migraine to reduce the frequency and severity of migraine attacks in patients with CM or EM who experience 4 or more migraine days per month. Fremanezumab is a fully humanized monoclonal antibody that targets calcitonin gene‐related peptide, a neuropeptide involved in the pathophysiology of migraine. Design/Methods: The 4 placebo‐controlled phases 2b and 3 studies included in this analysis were 16‐week, multicenter, randomized, double‐blind, placebo‐controlled, and parallel‐group studies consisting of a screening visit, a 28‐day pretreatment baseline period, and a 12‐week treatment period with a final evaluation 4 weeks after the final dose of the study drug. Safety endpoints included adverse events (AEs) and immunogenicity. Results: A total of 2566 patients were randomized across all studies (fremanezumab, n = 1704; placebo, n = 862), and 2563 patients were treated. Common reasons for study discontinuation were withdrawal by patient (n = 78), patient lost to follow‐up (n = 60), and AE (n = 50). The mean (standard deviation) duration of exposure was 83.8 (13.6) days for the patients who received fremanezumab, with a total exposure of 390.4 patient years and maximum exposure of 181 days. AEs were mostly mild to moderate in severity and were reported among 48‐69% of patients in all treatment groups, and most were injection site reactions (pain, induration, and erythema). Two deaths occurred (chronic obstructive pulmonary disease and intentional overdose of diphenhydramine), both of which were deemed unrelated to study drug by the investigators and sponsor. Cardiovascular adverse events, abnormal liver function tests, and hypersensitivity were uncommon and occurred at similar rates between the placebo and fremanezumab groups. Conclusions: Fremanezumab is a generally safe and well‐tolerated preventive therapy for migraine in adults.